Application of the Cooperative Learning Model Using the Gallery Walk Method to Improve Cognitive Learning Outcomes on the Solar System Topic - Nadila, Anisa; Rahmad, M.; Ma’ruf , Zuhdi (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Natural Science is an important subject that connects scientific concepts with real-life contexts. However, students’ cognitive learning outcomes at SMPN 45 Pekanbaru remain relatively low due to the application of teaching methods that are not yet optimal and unengaging learning media, particularly in the Solar System topic, which is inherently abstract. This study aims to describe students’ cognitive learning outcomes and to determine the improvement in learning outcomes after the application of a cooperative learning model using the Gallery Walk strategy. This research employed a quasi-experimental design with a posttest-only control group design. The population consisted of all seventh-grade students of SMPN 45 Pekanbaru, comprising four classes with a total of 160 students. The sample was selected using simple random sampling, resulting in two homogeneous classes totalling 80 students. The instrument used was a written cognitive learning test consisting of 20 multiple-choice questions. Data were analyzed using descriptive and inferential statistical analyses. The results showed that the experimental group recorded a mean score of 81, which fell into the good category, whereas the control group showed a comparatively lower average score. Inferential analysis using the Mann–Whitney test indicated a statistically meaningful difference in students’ cognitive learning outcomes between the experimental and control classes (Asymp. Sig. = 0.001 < 0.05). Therefore, the application of the Gallery Walk method has proven to be effective and feasible for improving the cognitive learning outcomes of seventh-grade students on the Solar System topic at SMPN 45 Pekanbaru. These findings suggest that the Gallery Walk method can serve as an alternative instructional strategy for science teachers to enhance students’ cognitive learning outcomes, particularly on abstract topics such as the Solar System.